STRATEGI RESILIENSI PELAKU PARIWISATA DALAMMENGHADAPI KRISIS COVID-19 DI KAWASAN PARIWISATA UBUD - Yanti, Ayu Suwita; Aditya, I Wayan Putra (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The emergence of the COVID-19 pandemic has paralyzed the tourism sector, especially the Ubud Tourism Area. The COVID-19 pandemic has been declared a non-natural national disaster. Ubud tourism actors carried out various strategies to survive the COVID-19 pandemic, and began to adapt to the new normal. This study analyzes the resilience strategy of tourism actors in dealing with the COVID-19 crisis in the Ubud Tourism Area. This study aims to examine the resilience strategies of Ubud tourism actors in dealing with difficult situations and the implications that arise due to the COVID-19 pandemic. This research was conducted in the Ubud tourism area with data collection locations in Ubud Central and Sayan Tourism Village. The relevant research approach used in this study is a qualitative approach with a case study research strategy. Data were collected through observation, interviews, and documentation. The results of this study concludes that the implementation of wellness tourism in Ubud greatly supports Ubud tourism, which had experienced a downturn due to the COVID-19 pandemic. The implications that arise due to the COVID-19 pandemic in the Ubud tourism area are changes in people's consumption patterns, the increasing development of wellness tourism, and the development of local businesses to support wellness tourism in Ubud.